A note on “Solving fully fuzzy linear systems by using implicit gauss–cholesky algorithm” - Malkawi, Ghassan; Ahmad, Nazihah; Ibrahim, H.; Albayari, Diya’ J. (Springer US, 2015)
This paper shows that the exact solutions for fully fuzzy linear systems for all examples in [1] are nonfuzzy solutions, and that the proposed solutions in [1] do not correspond to these systems.In addition, approximate fuzzy solutions are provided for all the examples.Finally, this paper shows the efficiency of the provided solutions by using the distance metric function introduced in [13].